(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Brick and mortar commercial vehicle organizations are adapting to work from home or remote working style. Organizations for a long time have been used only to a physical nature of work and not remote working especially in the commercial vehicle space in India. While this transition is a big change, there are definitive challenges in proving Learn from Home initiatives considering volatility, ambiguity, uncertainty and complexity of the of the environment. While organization who were already in the digital learning space are transitioning to the Learn from Home way, it has been hard for organizations who don’t have learning management systems and digital collaboration tools. Anxiety management of executives and providing digital awareness for successfully taking up learning remotely are the key during difficult times. It’s also very important to sustain the learning agenda keeping in mind various restrictions like social distancing norms and operating in frugal budgets. Learning during this time apart from being a capability building tool is also thought of as an engagement tool.